Strengthening the biogas sector of Ethiopia through international collaboration: the case of Digital Global Biogas Cooperation (DiBiCoo) - Bogale, Wondwossen; Misikir, Maya F.; Sewnet, Bruck; Laere, Ann-Kathrin van; Sagala, Saut; Ma, Chuan; Hilbert, Jorge Antonio; Mohammed, Mutala; Salie, Yaseen (IOP Publishing, 2024)
Even though biogas technology was introduced in Ethiopia in 1957, the technology is still in its infancy stage with more than 98 % of biogas plants installed in Ethiopia at a small- scale level and used for cooking and lighting applications. The Digital Global Biogas Cooperation (DiBiCoo) project facilitates collaboration between European biogas industries and stakeholders from emerging and developing markets through the development and application of innovative digital and non-digital support tools, knowledge transfer and capacity building. The Digital Global Biogas Cooperation helped the Ethiopian biogas sector through capacity building trainings, creating a digital biogas and gasification matchmaking platform to link companies with local biogas actors in the country, and assisting demo case projects up to prefeasibility study stage. Furthermore, it provided practical exposure through virtual and in person biogas plant tour in several countries, and generating several documents related to the Ethiopian biogas sector including an assessment on biogas potential, financial options and a legal frame work to assist the sector. Based on this collaboration, more than 30 stakeholders participated in 11 web seminars, 2 capacity-building trainings, 3 days business model development training in Biogas and more than 10 virtual study tours. One demo case and three- follower cases prefeasibility studies were supported. Thus, the Digital Global Biogas Cooperation is providing much needed support to the biogas sector of Ethiopia.